Lubricidade de biodiesel e sua associação com a vibração e nível de pressão sonora oriundos do contato esfera-plano sob deslizamento alternado - Farias, Aline Cristina Mendes de (2015)
The lubricity of biodiesel interferes in the normal operation of diesel injection systems, especially in nozzles. It can reduce the wear and raise the lifetime of the engine supply line. The method HFRR (High Frequency Reciprocating Rig) is a standard test for evaluation of diesel/ biodiesel lubricity (ASTM D6079). The HFRR lubricity evaluation mainly consists of measuring the printed scar wear on the ball. When wear is developing, some dynamic features of the system vary and it results in significant changes in the patterns of vibration, sound pressure level (SPL) and friction signals. The acquisition and characterization of signatures of these signals obtained during tribological tests are an important non-intrusive tool for evaluating of the lubricity of these fuels, whose representation in the time domain not always reveals trivial information. This requires signal transformation to the frequency domain using the Fast Fourier Transform (FFT) and Short-Time Fourier Transform (STFT) analyses. This thesis aimed to develop a dynamic assessment of lubricity fuels (Diesel S50, Methyl Ester of Soybean and B10 and B20 blends) in HFRR bench (ball-on-flat disk contact), and improving the methodological framework of ASTM D6079 standard by application of signal analysis techniques (vibration and SPL) and its association with parameters provided by ASTM D6079 (wear scar diameter) lasting 75, 120 and 180 minutes. The profiles and topographic parameters of scars and their microscopic analysis were used to further evaluate the influence of the time and fuel in the wear evolution of disk. In this evaluation, the fuel lubricity was influenced by increasing of biodiesel content and decreasing of number of cycles applied. From the temporal and frequency spectrum analysis of the vibration and NPS signals it is shown that both vibration and NPS stablish a relation with fuel lubricity, biodiesel content, number of cycles and parameters of profiles from scar of discs.